2014
DOI: 10.1542/peds.2013-2174
|View full text |Cite
|
Sign up to set email alerts
|

Care Coordination and Unmet Specialty Care Among Children With Special Health Care Needs

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Parents of children with special health care needs and low-income children report more unmet specialty care needs. Care coordination is associated with increased and decreased referrals to specialty care, but whether care coordination is related to unmet needs is unknown.WHAT THIS STUDY ADDS: Among children with special health care needs, care coordination is associated with lower odds of unmet specialty care needs regardless of whether care coordination was received within a medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
63
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 36 publications
1
63
0
1
Order By: Relevance
“…The international literature further states that creating an integrated healthcare service network and coordinated care optimize access to services and inputs, reduce the volume of emergency care and hospitalizations, and lower hospital costs (23)(24) . Another facilitating factor mentioned is solidarity among the mothers of technology-dependent children, creating a new support network.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The international literature further states that creating an integrated healthcare service network and coordinated care optimize access to services and inputs, reduce the volume of emergency care and hospitalizations, and lower hospital costs (23)(24) . Another facilitating factor mentioned is solidarity among the mothers of technology-dependent children, creating a new support network.…”
Section: Discussionmentioning
confidence: 99%
“…The literature values the exercise of these professionals, as they develop the knowledge and practices required to coordinate home-care (23) , with the family as the unit of care (20) . However, multi-disciplinary models are indicated to address the multiple facets of chronic conditions, with a better understanding of the psychosocial needs of these families (1,12) .…”
Section: Discussionmentioning
confidence: 99%
“…24,30 Care coordination often becomes a challenge for CSHCNs because of the severity or complexity of their chronic conditions, requiring multiple specialists and services. 31 The measure of care coordination addresses access to mental health providers and specialists and also to nonmedical services, such as early intervention programs, schools, and special education. Studies have also shown that family-centered communication is tied closely with effective care coordination, 24,32 and differences in cultural understanding of the health care system by foreignborn parents may influence care coordination.…”
Section: Discussionmentioning
confidence: 99%
“…obtained personally from some parents are listed in table 5. Boudreau et al [27] recently reported on care coordination for CSHCN and suggested that substantial payment reform will be needed for care coordination to be widely available. …”
Section: Discussionmentioning
confidence: 99%
“…It has been documented that families with less education (no education above high school level) and lower household incomes have a greater likelihood of having unmet specialty health care needs than those that are more educated and/or have higher household incomes [27]. Recommendations have been made that CSHCN and their families receive medical care in a medical home, since lack of a medical home has been associated with increased risk of foregone or delayed care [15].…”
Section: Discussionmentioning
confidence: 99%